Pengaruh Zakat dan Investasi Terhadap Pertumbuhan Ekonomi di Jawa Timur Tahun 2016-2020 - Windrayati, Dewi Ayu; Amijaya, Rachmania Nurul Fitri (IJABAH, 2024)
This study aims to determine how the influence of zakat and investment on economic growth in East Java in 2016-2020. The research approach uses a quantitative approach. Using a population of 38 regencies / cities in East Java Province. The data analysis method used uses panel data regression which shows the results that the zakat variable has no significant effect on economic growth in East Java in 2016-2020. Meanwhile, the investment variable has a significant effect on economic growth in East Java in 2016-2020. These results show the importance of increasing awareness to implement zakat in the community so that it can have an influence not only regionally but also nationally.